Modern Tools and Techniques of Employee Training in the Era of Remote Work and Education - Joanna LISOK (Communications of International Proceedings, 2020)
In the twenty-first century a manager should be characterized by excellent performance, experience, supported by knowledge and knowledge of modern information technologies. Virtual reality (VR) is a three-dimensional image that was created by computer. VR can represent different objects, objects and even whole events. Depending on the concept, virtual reality is based both on elements of the real world and completely fictional. The easiest way to say it is to say that this term simply means a virtual imitation of reality. VR is the ideal solution in cases where the implementation could actually be extremely expensive or particularly dangerous. So now it can be used, for example, for various types of training of future pilots, or conducting surgery classes in medical studies. In such situations, virtual reality allows you to gain a real and valuable experience in a virtual and maximum safe world. In most cases it is also the most economical solution. More and more often in the field of logistics or management engineering effective methods of training management and employees are sought. The young generation born in the era of modern IT solutions is more willing to undertake training based on modern solutions. One of them is the application of so-called augmented reality (AR), which combines the real world with the virtual world. The AR usually uses the image from a camera and then overlays the computer generated 3D elements on it. Nowadays, AR is used, similarly to VR, in aviation, medicine or automotive, as well as for marketing purposes, e.g. in applications for smartphones, which allow users to virtually change the color of the walls, or to place furniture from a given store in the room. There is no doubt that virtual reality is a technology that will be further developed - both in terms of entertainment and applications in various industries. The ability to combine modern technologies and proven Lean management methods is undoubtedly a desirable feature among managers. In the article, the author will characterize the methodology of effective training of employees, with an indication of the group of society that shows particular predispositions for effective education.
Keywords: Silesian University of Technology; Gliwice; Poland